Influence of EHD on transportation of ferric water nanofluid within permeable space. (26th May 2021) - Yao, Shao-Wen; Almarashi, Adel; Selim, Mahmoud Mohamed; Li, Zhixiong; Vuong, Bui Xuan
Abstract: This modeling article incorporated the CVFEM in demonstrating EHD forced convection of ferrofluid within a tank assuming variable permeability. Although this method has good accuracy in various approaches of modeling nanomaterial, the homogeneous model was selected in current effort. Plots, contours and formulas were exhibited as outputs. Rise of permeability guides to the augmentation of Nu which is related to higher speed of nano powders in media with higher Da. Thinner boundary is appeared with rise of Δ φ and more complex isotherms can be seen which guides to higher Nu. If radiation term added in energy transportation, greater magnitude of Nu will be obtained. Additionally, augmenting Rd, make the influence of Da more sensible. Slope of changing Nu with altering Δ φ augments for region with higher permeability. Growth of Rd yields to higher Nu and the slop of profile is unchanged with impose of EHD.